CURRENT STATE OF THE ART OF DILATED CARDIOMYOPATHY - Vakhidova Ikbolkhon Kholmurod qizi (Scholar Express Journals, 2023)
This article based on disease “Cardiomyopathy which is an acute, subacute or chronic lesion of the heart muscle of unknown or unclear etiology, often combined with damage to the endocardium, and sometimes the pericardium.” His basic research has made significant contributions to the study of cardiomyopathy. In subsequent years, heated discussions arose about the nature of this disease and its classification, which served as the reason for the creation in 1980 of a committee for the study of ILC. Depending on the leading pathophysiological mechanism or, if possible, etiological (pathogenetic) factor, they are divided into four forms: dilated, hypertrophic, restrictive CMP and arrhythmogenic right ventricular CMP. Along with four nonspecific cardiomyopathies, including dilated, hypertrophic, restrictive, right ventricular arrhythmogenic dysplasia, as before, specific cardiomyopathies were identified and unclassified cardiomyopathies.
Keywords: Cardiomyopathy; congestive cardiomyopathy; morphofunctional types; pharmacotherapy